Maize NPF6 Proteins Are Homologs of Arabidopsis CHL1 That Are Selective for Both Nitrate and Chloride. Issue 10 (8th September 2017) - Wen, Zhengyu; Tyerman, Stephen D.; Dechorgnat, Julie; Ovchinnikova, Evgenia; Dhugga, Kanwarpal S.; Kaiser, Brent N.
Abstract : Maize NPF6 proteins transport both nitrate and chloride with different specificity and activity that is influenced by the presence or absence of a proposed nitrate-binding His residue in NPF6. Abstract: Nitrate uptake by plant cells requires both high- and low-affinity transport activities. Arabidopsis thaliana nitrate transporter 1/peptide transporter family (NPF) 6.3 is a dual-affinity plasma membrane transport protein that has both high- and low-affinity functions. At-NPF6.3 imports and senses nitrate and is regulated by phosphorylation at Thr-101 (T101). A detailed functional analysis of two maize ( Zea mays ) homologs of At-NPF6.3 (Zm-NPF6.6 and Zm-NPF6.4) showed that Zm-NPF6.6 was a pH-dependent nonbiphasic high-affinity nitrate-specific transport protein. By contrast, maize NPF6.4 was a low-affinity nitrate transporter with efflux activity. When supplied chloride, NPF6.4 switched to a high-affinity chloride selective transporter, while NPF6.6 had only a low-affinity chloride transport activity. Structural predictions identified a nitrate binding His (H362) in NPF6.6 but not in NPF6.4. Mutation of NPF6.4 Tyr-370 to His (Y370H) resulted in saturable high-affinity nitrate transport activity and nitrate selectivity. Loss of H362 in NPF6.6 (H362Y) eliminated both nitrate and chloride transport. Furthermore, alterations to Thr-104, a conserved phosphorylation site in NPF6.6, resulted in a similar high-affinity nitrate transport activity with increased K m, whereas equivalent changes in NPF6.4 (T106) disrupted high-affinity chloride transport activity. NPF6 proteins exhibit different substrate specificity in plants and regulate nitrate transport affinity/selectivity using a conserved His residue.